Assessment of the environmental impacts generated by cocoa cultivation biomass in edible mushroom fruiting - A. D. Rincon-Quintero; Zirley Ardila-Caballero; Mauricio Ruiz-Ochoca; W. L. Rondon-Romero; Leidy Mejia-Casadiego; Luis Alfonso Del Portillo-Valdes (Heritage and Sustainable Development)
Based on a bibliographic review of articles and scientific documents regarding the composition of cocoa pod husk (CPH), the benefits of its use as a substrate, and the parameters required for the production of edible mushrooms, an environmental assessment for the operation phase was conducted. A total of 85 environmental aspects were identified, along with 85 direct impacts and 117 indirect impacts related to various environmental components. However, after reviewing the entire project phase, the environmental impacts were reduced to 38. Additionally, the utilization of CPH generates employment and economic income for the community, although it requires high consumption of water, energy, and fuel. The environmental categorization of the project indicated that it is a moderate-impact project, where its effects do not spread beyond the direct area of influence.